Movement‐related activity during goal‐directed hand actions in the monkey ventrolateral prefrontal cortex. (21st September 2015) - Simone, Luciano; Rozzi, Stefano; Bimbi, Marco; Fogassi, Leonardo
Abstract: Grasping actions require the integration of two neural processes, one enabling the transformation of object properties into corresponding motor acts, and the other involved in planning and controlling action execution on the basis of contextual information. The first process relies on parieto‐premotor circuits, whereas the second is considered to be a prefrontal function. Up to now, the prefrontal cortex has been mainly investigated with conditional visuomotor tasks requiring a learned association between cues and behavioural output. To clarify the functional role of the prefrontal cortex in grasping actions, we recorded the activity of ventrolateral prefrontal (VLPF) neurons while monkeys ( Macaca mulatta ) performed tasks requiring reaching–grasping actions in different contextual conditions (in light and darkness, memory‐guided, and in the absence of abstract learned rules). The results showed that the VLPF cortex contains neurons that are active during action execution (movement‐related neurons). Some of them showed grip selectivity, and some also responded to object presentation. Most movement‐related neurons discharged during action execution both with and without visual feedback, and this discharge typically did not change when the action was performed with object mnemonic information and in the absence of abstract rules. The findings of this study indicate that a population of VLPF neurons play a role in controlling goal‐directed grasping actions in several contexts. This control is probably exerted within a wider network, involving parietal and premotor regions, where the role of VLPF movement‐related neurons would be that of activating, on the basis of contextual information, the representation of the motor goal of the intended action (taking possession of an object) during action planning and execution. Abstract : The findings of this study indicate that a population of ventral prefrontal (movement‐related) neurons plays a role in controlling goal‐directed grasping actions in several contexts. The role of these neurons would be that of activating, based on contextual information, the representation of the motor goal (taking possession of an object) of the intended action during action planning and execution. This role is likely exerted within a wider network, involving parietal and premotor regions.